ADSORPTION OF TRITIUM FROM AQUEOUS SOLUTIONS OF TREATED CLAY MINERALS - Pushkarev, O.; Rudenko, I.; Skripkin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Experimental research was performed to evaluate the effect of porous and adsorption water on the ability of the clay minerals to extract tritium from aqueous solutions. Two series of experiments were performed in a closed system "clay mineral – tritiated water". In each series representatives of the main structural types of clay minerals are used: kaolinite (structural type 1:1), montmorillonite and saponite (structural type 2:1), palygorskite and sepiolite (ribbon-channel structural type). In the first series of experiments, the clay samples were not thermally treated. In the second series of experiments, the clay samples were thermally treated at 110°С. The duration of the whole experiment was 6 months. The results show that thermal treatment improves the tritium adsorption of the clay minerals. The portion of tritium that is extracted from the tritium water (designated as Kn) was greater in thermally treated clay samples for all the structural types used. Determined are the most efficient extractors of tritium from an aqueous solution, with a value of Kn = 52% (montmorillonite) and 53% (sepiolite). These results clearly demonstrate the benefits of thermal treatment of the clay minerals for increasement of their tritium extraction efficiency as the tritium adsorbents in water solutions.
Keywords: kaolinite; montmorillonite; saponite; palygorskite; tritiated water; heat treatment; storage of tritium